DAYA INSEKTISIDA ALAMI KOMBINASI PERASAN UMBI GADUNG (Dioscorea hispida Dennst ) DAN EKSTRAK TEMBAKAU ( Nicotiana tabacum L) (The Natural Insecticide Capacity of Squeeze Combination of Cassava (Dioscoreahispida Dennst) and Tobacco’s Extract (Nicotiana t) - Hasanah, Misroul; Tangkas, I Made; Sakung, Jamaluddin (Jurnal Akademika Kimia, 2012)
The research regarding the natural insecticide capacity of squeeze combination of cassava (dioscoreahispida Dennst) and tobacco’s extract has been done. The purposes are to measure the capacity of squeeze combination of cassava and tobacco’s extract as a natural insecticide and to determine the most effective combination as natural insecticide. The method was the laboratory experiments by using squeeze cassava and tobacco’s extract with the comparison ratio (in mL) as follow; 0:100, 25:75, 50:50, 75 : 25, and 100 : 0. The using of various comparisons is to determine the most effective combination as natural insecticide. The data were analyzed by the statistical test analysis of variance (ANOVA) with a 95% confidence level. The result shows that the squeeze combination of cassava and tobacco’s extract reduce the capacity of natural insecticide which is dioscorin compound in cassava and nicotin in tobacco.However, the most effective treatment to kill rice pest is the mixture of cassava and tobacco 0 mL : 100 mL, and also 100 mL : 0 mL.